Pengaruh Model Problem Based Learning terhadap Kemampuan Berfikir Siswa pada Tema Cita-Citaku Kelas IV MIS Alhusna - Delfi Handriani Harahap; Ahmad Landong (Jurnal Dirosah Islamiyah, 2023)
The study aims to determine whether the problem based learning (pbl) model affect students critical thinking skills in the theme of class IV MIS ALHUSNA. The research method used is experimental research. The subjects of the study were is class IV-A and class IV-B as many as 51 students. Data collection techniques in this study used test and non-test techniques. Research instrument in the form of observation sheets, questionnaires and also pre-test and post-test. The result showed that there is an influence of problem based learning models on students critical thinking skill. This is evidenced by the result of the hypothesis test using the t-test formula of an independent sample, obtained values thitung = 3,52 and values ttabel = 1,67. therefore thitung > ttabel = 3,52 > 1,67, this means that there is an influence of the problem based learning (PBL) learning model on students critical thinking skill in thematic subject on the theme of my ideas for grade IV students of MIS ALHUSNA the average score of the experimental class is higher that the control class, where the experimental class is 68.5 and the control class is 52,4, so it can be seen that the critical thinking skill of students in the experimental class who are treated in the form of a problem based learning (PBL) learning model are much better compared to the control class that was not given treatment Keywords : problem based learning model, critical thinking skill, experimental research